Design and Build a System for Procurement of Office Stationery Needs at Hasna Invitation - Hifzillah Hifzillah; Sharyanto Sharyanto; Bernadus Gunawan Sudarsono (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2023)
Office stationery is a very important item in the company as a tool to support company performance, the existence of office stationery equipment certainly greatly supports the performance of employees in the company. Hasna Invitation is a small business engaged in making physical wedding invitations or e-invitations and banners. Not only wedding invitations in Hasna Invitation, but children's toys in the form of puzzles. In meeting the needs of office stationery, Hasna Invitation is still not computerized so that each process is still not effective and efficient and data storage is also not well coordinated. From the description of the problems that occur, it is designed and built an Information System for Procurement of Office Stationery Needs which is expected to solve existing problems. For analysis and design methods used Unified Modeling Language (UML) and System Development Life Cycle (SDLC). The event program management information system uses the PHP programming language and MySQL as the database.